Pengaruh Kualitas Sistem Informasi Akuntansi pada Profitabilitas dengan Ketidakpastian Tugas sebagai Variabel Pemoderasi - Yogiswara, Gede Hara; Sadha Suardikha, I Made (E-Jurnal Akuntansi; Vol 25 No 3 (2018)DO - 10.24843/EJA.2018.v25.i03.p01, 2018)
The purpose of this study was to provide empirical evidence of the effect of the quality of accounting information systems (SIA) and to provide empirical evidence of the effect of task uncertainty in moderating the effect of SIA quality on profitability. This study uses the dependent variable that is profitability measured using ROA proxy. The independent variables used, namely the quality of the SIA measured using 10 statements with a 5-point Likert scale, and the moderating variable using task uncertainty measured using 4 5-point Likert scale statements. The population in this study is all LPDs located in Denpasar City. The sample determination technique used is saturated sample technique so that the sample in this study amounted to 35 LPDs. The analysis technique used is simple linear regression analysis technique and MRA. The results showed that the quality of accounting information systems had a positive effect on LPD profitability and task uncertainty showed statistically able to moderate the effect of accounting information system quality on profitability.